Người Khmer ở Nam Bộ, Việt Nam = The Khmer in the South of Vietnam - Đặng Thị Kim Oanh; Nguyễn Khắc Cảnh; Vũ Quốc Khánh; Phạm Ngọc Tuân; Lê Thị Mỹ Dung; Phạm Đình An; Johnson, Pete (Thông tấn, 2012)
Tìm hiểu nguồn gốc lịch sử, bản sắc văn hoá, phong tục lễ hội của dân tộc Khơ Me ở Nam Bộ